Undemocratic Response Towards "Deviant" Judgement and Fatwa: Sunni-Shiite Conflict in Sampang, Madura, East Java - Widyantoro, Hary (Mazahib, 2017)
AbstractThe study discusses how civic groups have judged other as "deviant" in the case of Sunni-Shiite conflict in Sampang, Madura,Â and how the state has responded to it.Â  The term â€œdeviantâ€ has been an important subject to study in Indonesia because it helps us to understand how certain communities other the others who are different in terms of religious understandings. This article argues that the state has undemocratically responded towards several groupsâ€™ judgment on Shiite in Sampang of being deviant; while Shiite community in Sampang are Indonesian citizen who are subject to the state protection. This situation is further exacerbated by the MUI recommendationÂ to the state to stop Shiite community from practicing their rituals, as it clearlyÂ violates religious freedom and democracy. This study uses secondary data in the forms of the MUI fatwa, Tajul Muluk case documentation in Catatan Keberagamaan by Center for Religious and Cross-cultural Studies, and the conflict escalation narration by previous scholars. As a study focused on the dynamic of the conflict, this paper helps scholars, activists, and government critically comprehend the relation between the state and civic groups before and during conflict escalation. Further, it becomes critical analysis towards the implementation of democracy in Indonesia.Keywords: Sunni-Shiite conflict, deviant sects in Indonesia, fatwa, Democracy